Educational choice and risk aversion: How important is structural vs. individual risk aversion? - Vanessa Hartlaub; Thorsten Schneider (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
According to sociological theories on educational choice, risk aversion is the main driving force for class-specific educational decisions. Families from upper social classes have to opt for the academically most demanding, long-lasting courses to avoid an intergenerational status loss. Families from lower social classes by contrast, tend instead to opt for shorter tracks to reduce the risk of failing in a long-lasting and costly education and, as a consequence, entering the labor market without a degree. This argument is deeply rooted in the social structure. Yet, the importance of individual risk preferences for educational choice has been neglected in sociology of education. We discuss these different forms of risk in the context of social inequalities in educational decision-making and demonstrate how they influence the intentions for further education of students attending the most demanding, academically orientated secondary school type in Germany. According to our argument, children from upper social classes are structurally almost compelled to opt for the academically most demanding educational courses, virtually without having a choice in the matter. In contrast, working class children do have to make an active decision and, thus, individual risk aversion comes into play for these students. For our empirical analyses, we rely on data from the youth questionnaire of the German Socio-Economic Panel Study (SOEP) collected in the years 2003 to 2010, and estimate multinomial logit models. Our empirical findings underline the importance of the structural risk aversion. Students with a higher social background are not only less sensitive to their school performance, but individual risk aversion is also completely irrelevant to their educational plans. The opposite applies to students with a lower social background: the more risk-averse they are, the more likely they are to opt for a double qualification rather than just a purely academic university degree course.
Keywords: I24; D81; Z13; 330; educational inequality; educational decision-making; risk aversion; tertiary education; vocational training; Jugendliche; Bildungsverhalten; Risikoaversion; Soziale Schicht; Deutschland